The Effectiveness Of Using Listen-Read Discuss (Lrd) Strategy Toward Student Reading Comprehension On Recount Text At Grade XI Of SMA Negeri 1 Pematangsiantar - Siadari, Grace; Sihombing, Partohap Saut Raja; Manihuruk, Leonita Maria Efipanias (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to explore the impact of the Listen Read Discuss (LRD) strategy on the reading comprehension abilities of eleventh-grade students at SMA Negeri 1 Pematangsiantar. Employing a quantitative approach, the research utilized a quasi-experimental design that includes two groups: an experimental class instructed using the LRD strategy and a control class taught without it. To evaluate the outcomes, the researchers administered both pretests and post-tests to each class. The findings revealed that the experimental class achieved mean scores of 54 in the pretest and 80.46 in the post-test, while the control class recorded mean scores of 53.21 and 71.21, respectively. With degrees of freedom calculated at 54 (28 + 28 - 2), the t-table value was 2.00, and the t-test value was 2.44. This indicated that the t-test exceeded the t-table (2.44 > 2.00), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. The application of the LRD strategy significantly enhances students' reading comprehension abilities concerning recount texts at SMA Negeri 1 Pematangsiantar.